PUBLIC ENTITIES THROUGH THE LOOKING GLASS: A DISCLOSURE ASSESSMENT STUDY ON ROMANIAN MUNICIPALITIES - OPRIȘOR, Tudor; NISTOR, Cristina Silvia (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
Recent trends in organizational reporting show that improved disclosure levels are increasingly important for public sector entities, as they employ publicly available resources in their activity and are accountable towards various impacted stakeholders. Thus, enhancing transparency is a mean to justify the use of and effects on the elements which have a significant role in the economic environment of the entity. This study aims to pinpoint the main elements of disclosure (of different complexity levels) in the case of Romanian municipalities, using public sources of data and determine the overall level of disclosure with a refined assessment model (linked with previouslydeveloped instruments). The added value of this study is the integrated approach of the disclosure assessment process for Romanian local public administration, focusing on both the financial and nonfinancial sides. The findings show that Romanian municipalities exhibit a level of transparency which is more elevated than expected – with sufficient instruments of disclosure publicly available, and the focus does not fall solely on financial information (although it is prioritized through the lens of accountability for the use of public funding).